Assessing the Validity of Self-Reports of Marijuana Use among Adolescents Entering the Juvenile Justice System: Gender Differences. (2nd January 2022) - Dembo, Richard; Wareham, Jennifer; Schmeidler, James; Wolff, Jessica
ABSTRACT: Objective : Scant research exists on the validity of self-reported marijuana use using biological assays among adolescents involved in the juvenile justice system. This exploratory study examined gender (sex) differences in underreporting of marijuana use and the impact of age, race/ethnicity, living situation, depression, family problems, sexual risk behaviors, previous drug treatment, and juvenile justice placement. Methods : Self-reports of past year marijuana use were validated with urinalysis, and those testing positive for marijuana use were selected for study. The sample was 256 females and 885 males, aged 12 to 18, entering an urban juvenile assessment center in a southeastern U.S. state between 2017 and 2019. Results : Results indicated significant differences in marijuana underreporting (tested positive but self-reported no use), with 37% of females and 55% of males underreporting use. For males, Hispanic ethnicity, African American race, sexually transmitted infection (STI), and secure detention placement increased the odds of underreporting, while having an incarcerate parent and previous drug treatment decreased the odds. For females, number of sexual partners decreased the odds of underreporting of marijuana use. Conclusion : These findings imply use of collateral information, such as urine tests, as a recommendation for juvenile justice intake to corroborate self-reports and guide risk assessment.